2008
DOI: 10.1194/jlr.r700019-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Review Series: Glycerolipids. Phosphatidylcholine and choline homeostasis

Abstract: Phosphatidylcholine (PC) is made in mammalian cells from choline via the CDP-choline pathway. Animals obtain choline primarily from the diet or from the conversion of phosphatidylethanolamine (PE) to PC followed by catabolism to choline. The main fate of choline is the synthesis of PC. In addition, choline is oxidized to betaine in kidney and liver and converted to acetylcholine in the nervous system. Mice that lack choline kinase (CK) a die during embryogenesis, whereas mice that lack CKb unexpectedly develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
249
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(257 citation statements)
references
References 96 publications
6
249
1
1
Order By: Relevance
“…In contrast to the present study, the plasma TAG concentrations were reduced in the mice fed the experimental diet despite the high fat and cholesterol levels (41). Choline is required for cell signalling and VLDL secretion from hepatocytes (42). Dietary choline as well as phosphatidylcholine has been shown to affect hepatic cholesterol homeostasis in rats, including increased excretion of cholesterol via the bile (43,44).…”
Section: Discussioncontrasting
confidence: 53%
“…In contrast to the present study, the plasma TAG concentrations were reduced in the mice fed the experimental diet despite the high fat and cholesterol levels (41). Choline is required for cell signalling and VLDL secretion from hepatocytes (42). Dietary choline as well as phosphatidylcholine has been shown to affect hepatic cholesterol homeostasis in rats, including increased excretion of cholesterol via the bile (43,44).…”
Section: Discussioncontrasting
confidence: 53%
“…Indeed, previous findings in PE methyltransferase knock-out mice fed a CD diet resulted in steatohepatitis due to low plasma membrane PC/PE ratio, which contributed to disrupted membrane integrity and decreased membrane fluidity (31). The observed outcome is intriguing as unlike MCD diet the MD diet contains an adequate choline level, which would be expected to drive the CDP-choline branch of the Kennedy pathway to synthesize PC de novo (11,32), although the PC synthesis from PE methylation would be predicted to be impaired due to the limitation of SAM. To account for this unexpected finding (decreased PC/PE ratio despite choline in the MD group), we observed that methionine deficiency increased hepatic ceramide levels in agreement with previous observations in PC12 cells (35) and in mice fed the MCD diet (37).…”
Section: Discussionmentioning
confidence: 90%
“…hyde is primarily formed through the mitochondrial oxidation of choline in the liver and kidney (47,48); hence, mitochondrial ALDH7A1 localization in liver and kidney is consistent with its role in betaine synthesis. To date, ALDH9A1 is the only other ALDH enzyme known to metabolize this substrate (1).…”
Section: Discussionmentioning
confidence: 93%